The Swedish green infrastructure policy as a policy assemblage: What does it do for biodiversity conservation?. Issue 2 (5th February 2023) - von Post, Maria; Knaggård, Åsa; Alkan Olsson, Johanna; Olsson, Ola; Persson, Anna Sofie; Ekroos, Johan
Abstract: Green infrastructure (GI) is increasingly used in policymaking to promote biodiversity and enhance ecosystem services through the protection, creation, restoration and connection of natural and man‐made green areas. The EU Commission adopted in 2013, the concept as a strategy. When member states apply the policy, it is translated into specific bureaucratic and political systems, creating different 'policy assemblages' of ideas and institutional features. We analyse the Swedish GI policy to draw conclusions about how it has been assembled in one particular member state and what that particular assemblage will imply for biodiversity conservation. In combination with understanding policies as assemblages, we use the 'What's the problem represented to be'‐approach as method. We show that the Swedish GI policy assemblage consists of a mix of policy ideas developed in Sweden and the EU. Despite the current strong focus on biodiversity conservation, the notion of land's multifunctionality, characterizing the EU strategy and the possibility to conserve biodiversity on land used for purposes other than conservation increasingly influence the Swedish policy as it is formed. Although the policy has the potential to mainstream biodiversity conservation measures across different sectors, based on our analysis of current discourse, its implementation will likely promote GI measures less disruptive to existing land use activities, making its capacity to halt biodiversity loss marginal. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Sammanfattning: Grön infrastruktur (GI) tillämpas allt oftare i policysammanhang i syfte att främja biologisk mångfald och stärka ekosystemtjänster genom att skydda, skapa, restaurera och sammanlänka naturliga och mänskligt anlagda gröna miljöer. EU kommissionen antog 2013 konceptet som en strategi. När medlemsstater tillämpar policyn, sker en tolkning till specifika byråkratiska och politiska system, vilket leder till olika policysammansättningar av ideér och institutionella egenheter. Vi analyserar den svenska policyn för grön infrastruktur för att dra slutsatser om hur policyn har satts ihop i en specifik medlemsstat och vad den kan medföra gällande bevarande av biologisk mångfald. Vi kombinerar förståelse av policys som en assemblage och metoden 'What's the problem represented to be' för att analysera materialet. Vi visar att den svenska policysammansättningen består av en blandning av policyideér som utvecklats i Sverige och i EU. Trots det nuvarande starka fokuset på bevarande av biologisk mångfald, har ideér om multifunktionella landskap vilket karaktäriserar EU policyn, fått ett ökande inflytande på den svenska policyn, allt eftersom den utvecklas. Även om policyn hyser potential att öka medvetenheten om behovet av bevarandeåtgärder för biologisk mångfald inom olika sektorer, visar vår analys av nuvarande diskurs att implementering av policyn troligt kommer att leda till bevarandeåtgärder med liten inverkan på nuvarande markanvändning, och därmed blir dess kapacitet att hindra förlust av biologisk mångfald marginell.